The role of the dietitian in the hospital team. The current situation in Poland in relation to the needs of society - Paulina Helisz; Weronika Gwioździk; Natalia Kaczmarczyk; Beata Całyniuk; Maria Kujawińska; Mateusz Grajek; Karolina Krupa-Kotara (Kazimierz Wielki University, 2022)
Background: Nutrition that is adequate to the patient's health status is a component of co-determining factors in improving the patient's health. Moreover, appropriate activities of a dietician, such as assessing the nutritional status or educating patients, are counted among the determinants conditioning the effectiveness of the conducted treatment. The number of employed dietitians in hospitals is low, which results in 76-740 patients per one specialist, which in turn makes effective education impossible. The aim of this study was to compare the duties of dietitians working in Polish hospitals in relation to the needs of the society. Material and methods: The research tool consisted of two original, anonymous questionnaires, addressed to the Polish public and to active dietitians. The analysis of results was based on 595 questionnaire results, including 93 from nutritionists. Results: Of the respondents who were admitted to the hospital ward, 83.3% had no contact with a nutritionist (N=347). The surveyed dietitians most often declared that there were two dietitians working at the health care provider employing them, with the smallest number being 1 and the largest number being 55. Only one in three respondents received dietary recommendations upon discharge from the hospital (N=133; 32.1%). Nearly half of dietitians do not prepare menus (48.4%). According to the public, a dietitian should be involved in nutritional counseling, developing menus for the hospital kitchen or catering, and nutritional recommendations for patients discharged from the hospital. Conclusions: Dietitians with the right qualifications and specialties, integrated into the health care workforce, can have a huge impact on the proper dietary therapy of patients. As a result, there is a high probability of increasing the effectiveness of treatment, resulting in health service savings and support for the medical community.